3D printing catalyst for preparing low-carbon olefin from carbon dioxide as well as preparation method and application of 3D printing catalyst
The porous columnar catalyst with a unique pore structure was prepared by 3D printing technology and treated in potassium hydroxide solution, which solved the problems of complex traditional catalyst preparation process and low mass heat transfer efficiency, and achieved efficient catalytic reaction of converting CO2 into low-carbon olefins.
Patent Information
- Application Number
- CN202411973186.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-30
AI Technical Summary
The preparation process of traditional CO2 low-carbon olefin catalysts is complex, with artificial errors, low mass transfer and heat transfer efficiency, resulting in low catalytic reaction efficiency.
Porous columnar catalysts with unique pore and transverse plate structures were prepared by 3D printing technology, catalyst precursors were printed by selective laser melting technology, and treated in potassium hydroxide solution to improve catalytic performance.
The catalyst preparation process is simplified, artificial errors are reduced, the disturbance of the reaction gas, the contact area between the catalyst and the raw material gas and the mass transfer and heat transfer efficiency are improved, and the catalytic reaction efficiency is significantly improved.
Smart Images

Figure CN119746858A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of catalysis, and in particular to a 3D printing catalyst for preparing low-carbon olefins from carbon dioxide, and a preparation method and application thereof. Background Art
[0002] Against the backdrop of global climate change and increasingly scarce resources, carbon dioxide (CO 2 ) has become an important direction of scientific research and technological innovation. 2 As a major greenhouse gas, its emission reduction and resource utilization are of great significance to alleviating a series of environmental problems such as global warming and ocean acidification. At the same time, low-carbon olefins (such as ethylene, propylene, etc.) as important chemical raw materials are widely used in industries such as plastics, rubber, and synthetic fibers, and the market demand is huge.
[0003] The traditional method of producing low-carbon olefins mainly relies on petroleum cracking, but this process not only consumes a lot of fossil resources, but also produces additional CO 2 Therefore, the development of CO 2 The new technology for preparing low-carbon olefins from raw materials not only helps to reduce greenhouse gas emissions, but also achieves the recycling of resources, and has important economic and environmental value.
[0004] CO 2 The traditional catalysts for producing low-carbon olefins as raw materials have the following shortcomings:
[0005] 1. Complex preparation process: Traditional catalyst preparation process usually involves multiple steps and processes, and requires strict condition control, which makes the preparation process cumbersome and time-consuming.
[0006] 2. Human errors exist in the preparation process: In the traditional catalyst preparation process, material processing (such as grinding, mixing, molding, etc.) usually relies on manual operation or simple mechanical equipment. These operations may cause errors due to the skill level of the operator and the accuracy of the equipment.
[0007] 3. Low mass and heat transfer efficiency: Traditional catalysts have a single particle size distribution, limited thermal conductivity and poor thermal stability in terms of mass and heat transfer efficiency. Summary of the invention
[0008] The purpose of the present invention is to solve the above-mentioned problems in the prior art and provide a 3D printed catalyst for preparing low-carbon olefins from carbon dioxide and a preparation method and application thereof. By designing a porous columnar catalyst with a unique pore and transverse plate structure, the catalyst is designed to enhance the disturbance of the reaction gas and enhance the catalyst and the raw gas (CO 2 and H 2) to improve the catalytic reaction efficiency. After the catalyst was printed using the selective laser melting (SLM) 3D printing technology, the catalyst precursor was treated with a KOH solution of a certain molar concentration. 2 It exhibits good catalytic performance in the hydrogenation reaction to produce light olefins, 2 In summary, the present invention overcomes the disadvantages of traditional catalysts in CO 2 The limitations of the conversion process can be overcome to achieve more direct and environmentally friendly production of low-carbon olefins.
[0009] In order to achieve the above object, the present invention adopts the following technical scheme:
[0010] A method for preparing a 3D printed catalyst for preparing low-carbon olefins from carbon dioxide comprises the following steps:
[0011] 1) Using alloy powder mainly composed of metallic iron as raw material, the iron-based catalyst precursor is printed by selective laser melting technology, and then cleaned, dried, and then calcined;
[0012] 2) soaking the catalyst obtained in step 1) in a potassium hydroxide solution;
[0013] 3) Drying and calcining the catalyst soaked in step 2).
[0014] The iron-based catalyst precursor has a porous columnar structure as a whole, consisting of two layers of inner and outer circular columnar structures, and both layers of the inner and outer circular columnar structures are provided with multiple channels; multiple vertical plates are arranged radiating from the center of the circle to the outer circular columnar structure, and multiple horizontal plates are arranged between the inner and outer circular columnar structures, and multiple channels are arranged equidistantly on each vertical plate and each horizontal plate.
[0015] In step 1), the calcination temperature is 500-900°C.
[0016] In step 2), the concentration of the potassium hydroxide solution is 0.1 to 1.5 mol / L.
[0017] In step 3), the calcination temperature is 500-900°C.
[0018] A 3D printing catalyst for preparing light olefins from carbon dioxide is prepared by the above-mentioned preparation method.
[0019] The application of the 3D printed catalyst for preparing low-carbon olefins from carbon dioxide is used for preparing low-carbon olefins by hydrogenating carbon dioxide, specifically using a high-pressure fixed bed reactor to prepare CO 2 Evaluation of hydrogenation reaction performance.
[0020] Compared with the prior art, the technical solution of the present invention has the following beneficial effects:
[0021] 1. The present invention uses 3D printing technology to prepare CO 2 Compared with the preparation of traditional catalysts, the present invention simplifies the process of preparing the catalyst.
[0022] 2. The present invention can accurately control the structure of the printed catalyst when preparing the catalyst, reducing the human error in the traditional catalyst preparation process. 3D printing technology can accurately prepare a catalyst suitable for CO 2 The unique pore structure catalyst for the production of low-carbon olefins and the control of the disturbance of the reaction gas flow and the surface area of the catalyst bed. The printed catalyst has high fidelity, good mechanical properties, high mass and heat transfer efficiency, and good chemical stability.
[0023] 3. CO of the present invention 2 The preparation of the low-carbon olefin printing catalyst uses iron-based alloy powder as raw material, which is different from the traditional CO 2 Compared with the production of low-carbon olefin catalysts, the preparation cost is cheap, which can greatly reduce the waste of raw materials, and the raw material powder can be reused, which can reduce energy consumption. These advantages are in line with the concepts of green chemistry and sustainable development, and have great application potential and prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 is a schematic diagram of the structure of the catalyst model of Example 1; wherein, Figure 1 A is a schematic diagram of the overall structure of the catalyst. Figure 1 B is a schematic diagram of the top view structure of the catalyst. Figure 1 C is a schematic diagram of the internal structure of the catalyst. Figure 1 D is a schematic diagram of the top view of C;
[0025] Figure 2 The product diagram of the uncalcined and calcined catalyst of Example 1; wherein, Figure 2 A and C are the overall structure and top view of the uncalcined catalyst; Figure 2 B and D are the overall structure and top view of the catalyst after calcination;
[0026] Figure 3 is the X-ray powder diffraction pattern of the catalyst in Example 1;
[0027] Figure 4 The performance diagram of the catalyst immersed in potassium hydroxide with different concentrations;
[0028] Figure 5 is a performance diagram of the catalyst at different calcination temperatures in step 7);
[0029] Figure 6 Performance diagram of catalysts soaked in different potassium compounds. DETAILED DESCRIPTION
[0030] In order to make the contents of the present invention easier to understand, the technical solution of the present invention is further described below in conjunction with specific implementation methods, but the present invention is not limited thereto.
[0031] Example 1
[0032] 1) Use solidworks software for auxiliary design and build digital models and tasks. The digital tasks include laser power, scanning rate, scanning path, slice thickness, etc. See the digital model Figure 1 , is a porous columnar catalyst (PCC), which consists of two layers of inner and outer circular cylindrical structures, and both layers of the inner and outer circular cylindrical structures are provided with multiple channels; multiple vertical plates are arranged between the inner and outer circular cylindrical structures radiating from the center of the circle, specifically, the inner and outer circular cylindrical structures are connected by 16 equally divided vertical plates (the inner circular ring is provided with 8 vertical plates, and the outer and inner circular rings are provided with 8 vertical plates), each vertical plate has 6 circular holes arranged equidistantly from top to bottom, and the outer and inner circular rings are provided with 8 vertical plates from top to bottom. Five horizontal plates are evenly arranged at equal distances, and the horizontal plates are staggered up and down, wherein the 1st, 3rd, and 5th horizontal plates are distributed on the inner side of the outer ring, and the 2nd and 4th horizontal plates are distributed on the outer side of the inner ring. Two circular holes are evenly arranged on the 1st, 3rd, and 5th horizontal plates at a 45° angle, and one circular hole is evenly arranged on the 2nd and 4th horizontal plates at a 45° angle; the outer ring corresponding to the two vertical plates has 12 circular holes evenly arranged from top to bottom, and the inner ring corresponding to the two vertical plates has 6 circular holes evenly arranged from top to bottom. The total height of the catalyst structure is 20mm; the diameter of the outer ring is 10.8mm; the diameter of the inner ring is 5.4mm; the thickness of all plates is 0.6mm, and the diameter of the circular hole is 1mm.
[0033] 2) 3D printing catalyst preparation was performed using 316L stainless steel alloy powder as raw material, and the 3D printer selectively laser melted the metal powder using pre-set parameters such as laser power, scanning rate, scanning path, and slice thickness;
[0034] 3) Using a wire cutting CNC machine tool, the sample printed in step 2) is cut and separated from the substrate, and the cut sample is cleaned with kerosene 2 to 3 times and naturally dried, and the porous columnar catalyst precursor is ultrasonically cleaned with ethanol and ultrapure water for 3 to 4 times, and then dried in a sample oven, the drying time is 12 hours, and the drying temperature is 60°C, to obtain a sample as shown in Figure 2 As shown in A and C;
[0035] 4) placing the sample obtained in step 3) into a porcelain boat and calcining it in a high-temperature muffle furnace at a temperature of 700° C., a heating rate of 5° C. / min, and a calcining time of 12 h;
[0036] 5) placing a batch of samples obtained in step 4) into 50 mL of 0.05 mol / L, 0.1 mol / L, 0.5 mol / L, 1.5 mol / L, and 7.0 mol / L KOH solutions respectively for 2 h;
[0037] 6) The sample obtained in step 5) was placed in a sample drying oven at 100° C. for 12 h;
[0038] 7) The sample obtained in step 6) was placed in a porcelain boat and calcined in a high-temperature muffle furnace at a calcination temperature of 700°C, a heating rate of 5°C / min, and a calcination time of 12h. Figure 2 The porous columnar catalyst shown in B and D is named PCC-M KOH-700, where M represents the molar concentration of KOH, and the values of M are 0, 0.05, 0.1, 0.5, 1.5, 7.0, and 700 represents the calcination temperature of 700°C. PCC-700 is a porous columnar catalyst obtained without soaking and calcined at 700°C.
[0039] Figure 3 The XRD pattern of the catalyst prepared in Example 1 is as follows. Figure 3 It can be seen that the iron oxide peak on the surface of the PCC-700 catalyst that has not been soaked is not obvious after calcination; however, after being soaked in KOH solution, iron oxide is more easily generated through calcination, indicating that soaking in KOH solution can promote the formation of iron oxide, form active sites on the catalyst surface, and affect CO 2 Catalytic activity for the production of light olefins.
[0040] Example 2
[0041] The difference between Example 2 and Example 1 is that the concentration of KOH in step 5) is fixed and the high-temperature calcination temperature in step 7) is different. The calcination temperature in step 7) of Example 2 ranges from 500 to 900°C, the heating rate is 5°C / min, the calcination time is 12h, and the other preparation steps are the same as those of Example 1. Finally, a porous columnar catalyst sample is obtained, and the catalyst is named PCC-0.5KOH-X (X represents the numerical value of the calcination temperature, and the value of X is 500, 600, 700, 800, 900).
[0042] Comparative Example 1
[0043] The difference between Comparative Example 1 and Example 1 is that in step 5), the soaking solution is 50 mL of 0.5 mol / L KCl, KOH and KNO 3The other preparation steps were the same as those in Example 1, and finally porous columnar catalyst samples were obtained. The catalysts were named PCC-0.5KCl-700, PCC-0.5KOH-700, PCC-0.5KNO 3 -700.
[0044] Application Examples
[0045] A 3D printed porous columnar catalyst sample with a total height of 20 mm and a diameter of 10.8 mm was loaded into a transparent quartz tube with an inner diameter of 12 mm. An appropriate amount of quartz wool was placed at both ends of the catalyst to fix the catalyst. The quartz tube was placed inside the reactor and fixed in a heating furnace for CO 2 Hydrogenation reaction performance test: After ensuring the air tightness of the device, H 2 Perform reduction pretreatment and accurately control H 2 After the reduction flow rate was 30 mL / min, the temperature was raised to 400 °C at a heating rate of 2 °C / min, and the in-situ reduction was carried out at 400 °C for 8 h. 2 After the reduction is completed, the temperature is lowered to room temperature, and the valve is cut to allow CO to flow in. 2 / H 2 / Ar mixed gas, the reaction flow rate was accurately controlled at 20mL / min by a mass flow meter, the reaction pressure was controlled at 3.0MPa by a back pressure valve, the temperature was raised to 300℃ at 2℃ / min to evaluate the performance of the catalyst, and the product after 8h of reaction was used for detection and analysis.
[0046] Figure 4 The catalyst obtained in Example 1 was heated in CO 2 The performance diagram of the hydrogenation reaction to produce light olefins shows that the performance of the porous columnar catalyst in KOH solutions of different molar concentrations is significantly different. When the porous columnar catalyst is not treated with KOH solution, the product distribution is mainly methane, and almost no light olefins are generated. At the same time, CO 2 The conversion rate and byproduct CO selectivity are low; as the molar concentration of KOH increases to 0.05 mol / L, CO 2 The conversion rate increased slightly, and the low-carbon olefins increased slightly to 3.5%; when the molar concentration of KOH was gradually increased to 0.1 mol / L, CO 2 The conversion rate increased to a certain extent, and the selectivity of light olefins increased significantly to 18.3%. When the molar concentration of KOH solution was further increased to 0.5 mol / L, CO 2 The conversion rate increased to 26.3%, while the selectivity of light olefins reached 34.5%, and the selectivity of byproduct CO also remained at a low level; as the molar concentration of KOH continued to increase to 1.5 mol / L and 7.0 mol / L, CO 2The selectivity and low-carbon olefin selectivity gradually decreased, while the by-product CO selectivity further increased. When the porous columnar catalyst was immersed in 7.0 mol / L KOH solution, the by-product CO selectivity reached 55.4%. Combined with the product distribution diagram, it can be observed that CO 2 The conversion rate first increases and then decreases with the increase of KOH molar concentration. 2 The conversion rate gradually increased from 16.3% to 26.3% and then gradually decreased to 16.7%. The by-product CO selectivity increased from 15.8% to 55.4%. The low-carbon olefin selectivity increased from 0.2% to 34.5% and then decreased to 26.9%. The porous columnar catalyst (PCC-0.5KOH-700) showed the best catalytic performance in a moderate KOH concentration of 0.5 mol / L.
[0047] Figure 5 The catalyst obtained in Example 2 was 2 Performance diagram of the hydrogenation reaction to produce light olefins. It can be seen from the performance diagram that the CO 2 The conversion rate was 11.4%, the selectivity of by-product light olefins was 73.3%, and the selectivity of light olefins was only 21.3%. As the calcination temperature gradually increased to 600 °C, CO 2 The conversion rate increased to 21.6%, and the selectivity of light olefins increased to 29.3%. When the calcination temperature was gradually increased to 700℃, CO 2 The conversion rate reached 26.3%, and the selectivity of light olefins reached 34.5%. As the roasting temperature continued to increase, CO 2 The conversion rate gradually decreases. When the calcination temperature reaches 900℃, CO 2 The conversion rate dropped to 15.2%, and the selectivity of light olefins dropped to 10.3%. 2 The conversion rate and light olefin selectivity showed a trend of first increasing and then decreasing with the increase of calcination temperature, and the by-product CO selectivity first decreased and then increased, showing the best performance when the catalyst calcination temperature was 700℃.
[0048] Figure 6 The catalyst CO obtained in Comparative Example 1 2 Performance diagram of the hydrogenation reaction to produce light olefins. It can be seen from the performance diagram that the 3D printed porous columnar catalyst (PCC-0.5KCl-700) obtained by treating with 0.5 mol / L KCl solution has a CO 2 The conversion rate was 21.4%, the selectivity of light olefins was only 18%, and the by-product CH 4 High selectivity; through 0.5mol / L KNO 3 PCC-0.5HNO obtained by solution treatment3 -700 catalyst for CO 2 The conversion rate is 20.1%, the selectivity for light olefins is 27.1%, and the selectivity for by-product CO is 46.1%. Comprehensively comparing the three different types of potassium compounds, PCC-0.5KOH-700 exhibits the best catalytic performance.
[0049] The 3D printed catalyst for preparing low-carbon olefins from carbon dioxide provided by the present invention is based on computer-aided modeling software, combined with metal 3D printing technology, using 316L stainless steel alloy powder as the basic printing raw material, and using selective laser melting (SLM) 3D printing technology to print out a catalyst precursor. The printed catalyst precursor is calcined, soaked in potassium hydroxide, and subjected to post-treatment operations such as drying and calcination to obtain a catalyst sample, which has good activity in preparing low-carbon olefins from carbon dioxide.
Claims
1. A method for preparing a 3D printed catalyst for preparing low-carbon olefins from carbon dioxide, characterized in that: The following steps are involved: 1) Using alloy powder mainly composed of metallic iron as raw material, the iron-based catalyst precursor is printed by selective laser melting technology, and then cleaned, dried, and then calcined; 2) soaking the catalyst obtained in step 1) in a potassium hydroxide solution; 3) Drying and calcining the catalyst soaked in step 2).
2. The method for preparing a 3D printing catalyst for preparing low-carbon olefins from carbon dioxide according to claim 1, characterized in that: The iron-based catalyst precursor is composed of two layers of inner and outer circular columnar structures, and both layers of the inner and outer circular columnar structures are provided with multiple channels; multiple vertical plates are arranged radiating from the center of the circle to the outer circular columnar structure, and multiple horizontal plates are arranged between the inner and outer circular columnar structures, and multiple channels are arranged equidistantly on each vertical plate and each horizontal plate.
3. The method for preparing a 3D printing catalyst for preparing low-carbon olefins from carbon dioxide according to claim 1, characterized in that: In step 1), the calcination temperature is 500-900°C.
4. The method for preparing a 3D printing catalyst for preparing low-carbon olefins from carbon dioxide according to claim 1, characterized in that: In step 2), the concentration of the potassium hydroxide solution is 0.1 to 1.5 mol / L.
5. The method for preparing a 3D printing catalyst for preparing low-carbon olefins from carbon dioxide according to claim 1, characterized in that: In step 3), the calcination temperature is 500-900°C.
6. A 3D printed catalyst for preparing low-carbon olefins from carbon dioxide, characterized by: Prepared by the preparation method according to any one of claims 1 to 5.
7. The use of a 3D printing catalyst for preparing light olefins from carbon dioxide according to claim 6, characterized in that: Used for hydrogenation of carbon dioxide to produce light olefins.
Citation Information
Patent Citations
Catalyst for preparing light olefin from synthesis gas and preparation method thereof
CN105854915A
Fe-based monolithic catalyst based on 3D printing, preparation method of Fe-based monolithic catalyst and application of Fe-based monolithic catalyst to preparation of low-carbon olefin by catalyzing CO2 hydrogenation
CN116920852A
Preparation method of Fe-based catalyst for preparing low-carbon olefin through CO2 hydrogenation
CN117358289A
Synthetic ammonia iron-based electrode catalyst for 3D printing as well as preparation and application of synthetic ammonia iron-based electrode catalyst
CN118441307A
Promoted skeletal iron catalysts for Fischer-Tropsch synthesis processes
US20020156137A1